An Epidemiological Investigation of Cholera Outbreak in a Residential School for differently abled children and adolescents in Central India - Gautam, Pragati; Goswami, VP; Bajpai, Ila; Sakalle, Salil; Dixit, Sanjay (Indian Journal of Community Health, 2025)
Background: Migration, inadequate sanitation, congestion, and disease ignorance make cholera a major public health issue in emerging nations like India. The increase in diarrhea and dehydration cases at an NGO Residential School for differently abled children and adolescents in Indore, M.P., India, demanded quick investigation to avert future morbidity and mortality. Objectives: To investigate diarrhea and dehydration outbreak at an NGO Residential School for differently abled children and adolescents in urban Indore, M.P., India; determine the etiological agents, outbreak’s severity and recommend control strategies. Materials and Methods: A cross-sectional study with pre-defined case definition, followed line-listing and collection of stool, food, and water samples. Symptomatic cases were referred and treated. A comprehensive epidemiological report with recommendations and inclusive action plan was submitted to the district health authorities. Results: Out of 94 suspected cases, 31 tested positive for cholera. Most affected individuals (72.34%) were aged 10–19 years, with an equal male-to-female ratio. The case fatality rate was 4.3%, while attack rate was 32.98%. Contaminated drinking water and poor hygiene were identified as the main causes of the outbreak. Conclusion: Contaminated water and poor hygiene were identified as key factors responsible for cholera outbreak. Water treatment and hygiene education helped control the outbreak. Periodic supervision suggested to prevent future outbreaks.